The Success of the Napiter Re-education Program on the Acceptance of the Republic of Indonesia: Narrative Literature Review - Thahir, Andi; Wiranto, Bambang Budi; Bahar, Nadya Cahyani (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Reeducation is a follow-up intervention that aims to provide re-understanding for terrorist prisoners. This study is a follow-up study conducted using a different approach. This study aims to determine whether various interventions in the re-education program have been successful in increasing the acceptance of terrorists in the Unitary State of the Republic of Indonesia. The research method used is the Narrative Literature Review (NLR), by assessing, identifying, analyzing and summarizing previously published literature. The re-education program in Indonesia with various interventions shows an increase in the acceptance of national values and acceptance of the unitary state of the Republic of Indonesia (NKRI) among terrorist prisoners in Indonesia. A holistic approach that includes psychological, religious education, social, and economic aspects has been shown to provide better results than methods that focus on one aspect only. Psychological interventions help prisoners manage emotions and stress, while moderate religious education directs them to an inclusive understanding of religion and skills through the training provided are factors that greatly support the acceptance of NKRI